Increased expression of glial fibrillary acidic protein fragments and μ-calpain activation within the hippocampus of prion-infected mice. (20th January 2006) - Gray, B.C.; Skipp, P.; O'Connor, V.M.; Perry, V.H.
Abstract : Prion diseases are characteristically accompanied by marked astrocytic activation, which is initiated relatively early in the disease process. Using the intracerebrally injected ME7 strain of prion agent to model disease, we identified an expected increase in GFAP (glial fibrillary acidic protein) but additionally noted an accumulation of GFAP cleavage fragments in hippocampal homogenates. A time-dependent increase in hippocampal μ-calpain immunoreactivity within astrocytes suggests that its proteolytic activity may account for the cleavage of GFAP that is observed in the ME7 model. It may therefore contribute to the reactive gliosis that is characteristic of prion diseases.